2020
DOI: 10.1093/mtomcs/mfaa011
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow synthesis and antimicrobial evaluation of NHC* silver carboxylate derivatives of SBC3 in vitro and in vivo

Abstract: N-Heterocyclic silver carbene compounds have been extensively studied and shown to be active agents against a host of pathogenic bacteria and fungi. By incorporating hypothesised virulence targeting substituents into NHC-silver systems via salt metathesis, an atom efficient complexation process can used to develop new complexes to target the passive and active systems of a microbial cell. The incorporation of fatty acids and an FtsZ inhibitor have been achieved, and creation of both the intermediate salt and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…N -heterocyclic silver carbene (NHC-silver) complexes have been recently found to be active agents in treating pathogenic infections, including cystic fibrosis and chronic lung infections ( Kascatan-Nebioglu et al, 2006 ; Hindi et al, 2008 ). We previously synthesized a new series of p-cyanobenzyl- and benzyl-substituted NHC-silver ( Patil et al, 2011 ), and SBC3 has been identified as the lead compound for the promising inhibition of MRSA in a murine thigh infection model ( O'Beirne et al, 2021 ). However, SBC3 alone has notable mammalian cell toxicity in a dose-dependent manner ( Patil et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N -heterocyclic silver carbene (NHC-silver) complexes have been recently found to be active agents in treating pathogenic infections, including cystic fibrosis and chronic lung infections ( Kascatan-Nebioglu et al, 2006 ; Hindi et al, 2008 ). We previously synthesized a new series of p-cyanobenzyl- and benzyl-substituted NHC-silver ( Patil et al, 2011 ), and SBC3 has been identified as the lead compound for the promising inhibition of MRSA in a murine thigh infection model ( O'Beirne et al, 2021 ). However, SBC3 alone has notable mammalian cell toxicity in a dose-dependent manner ( Patil et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…As promising bactericidal leads N-heterocyclic carbene (NHC)-silver(I) complexes, such as SBC3 [1,3-dibenzyl-4,5-diphenyl-imidazol-2-ylidene silver(I) acetate], possess a reversible, high affinity for inhibition of bacterial thioredoxin reductase (bTrxR); while they have no significant inhibitory effect on mammalian (mTrxR) ( O'Loughlin et al, 2021 ), making it a potential antibacterial candidate. However, although our previous assays showed that SBC3 can efficiently inhibit bacterial cell growth ( O'Loughlin et al, 2021 ; O'Beirne et al, 2021 ; Sharkey et al, 2012 ), the high mammalian toxicity of SBC3 with unknown mechanisms restricted its application.…”
Section: Introductionmentioning
confidence: 99%
“…1 ), isolated by the Tacke group via Young's synthetic method, has shown excellent inhibitory activity against a selection of resistant bacterial and fungal pathogens, both in vitro and in vivo using the Galleria mellonella insect model. 44 , 46 , 47 SBC3 promoted G. mellonella survival against S. aureus and C. albicans infections, without displaying any adverse effects at the test concentrations, whilst subsequent studies in a murine thigh infection model showed both good tolerability and decreased dissemination of MRSA in response to SBC3 concentrations at the appropriate dosing regimen. 46 , 47 The aim of the work presented here was to apply label-free quantitative mass spectrometry (LFQ MS) to C. parapsilosis exposed to SBC3 to characterize the proteomic alterations induced by the complex, determine the anti-virulence activity, and thus gain an insight into its antifungal mode(s) of action.…”
Section: Introductionmentioning
confidence: 93%
“…The new technologies and modern trends in the synthesis of drugs and natural products that have been developed by academia and industry are opening up opportunities on a scale previously considered unattainable in most laboratories and production lines. The use of high-throughput and breakthrough technology platforms, particularly flow chemistry and process analytics (PAT), is representative of the endless potential in the pharmaceutical field and the improvements over the current state that are possible ( Figure 1 ) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%